Tailored Target Ablation Index Guided Pulmonary Vein Isolation in Treating Paroxysmal Atrial Fibrillation: A Single Center Randomized Study in Asian Population (AI-Asian-I) - Xiong, Qingsong; Liao, Jia; Chen, Weijie; Xiao, Peilin; Du, Huaan; He, Qushuai; Yin, Yuehui; Ling, Zhiyu; Chen, Shaojie (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: To evaluate the efficacy and safety of a lower ablation indexes (AI) guided pulmonary vein isolation (PVI) in treating paroxysmal atrial fibrillation (AF). Methods: Ninety patients with paroxysmal AF scheduled for radiofrequency ablation were randomly divided into three groups. The AI targets for PVI were as follows: In group A/B/C, 550/500/450 for roof and anterior wall, and 400/350/300 for posterior/inferior wall. The first-pass PVI rate, ablation time, complications and recurrence of atrial tachyarrhythmia (ATa) were compared. Results: The patients’ mean age was 62.5 years (male: 63.3%). The baseline characteristics were comparable. There was no significant difference in the first-pass PVI rate among the three groups (right-sided-PV: 70% vs.83.3% vs.73.3%, P=0.64; left-sided-PV: 66.7% vs.80% vs.73.3%, P=0.51), also with similar gap rate during the procedural waiting time. At one-year follow-up there was no significant difference in the recurrence rate of ATa among the three groups (10% vs.13.3% vs.13.3%, P = 1.00). The ablation time in the Group C was significantly less than that in the other two groups (47.8min. vs.47.0min. vs.36.6min, P < 0.001). Higher AI seemed to link a non-significant trend towards higher rate of pericardial effusion/tamponade (group A+B vs. group C：6.7% vs. 0%, P=0.30), although the rate of overall complications was not different among the three groups. Conclusion: This randomized study shows that, a relatively lower target AI guided ablation may be similarly effective to achieve PVI with significantly reduced ablation time and obtain similar clinical outcome in treating paroxysmal AF in Asian population.